2006
DOI: 10.1002/syn.20315
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response analysis of locomotor activity and stereotypy in dopamine D3 receptor mutant mice following acute amphetamine

Abstract: Accumulating evidence suggests that dopamine D3 receptor (D3R) stimulation is inhibitory to spontaneous and psychostimulant-induced locomotion through opposition of concurrent D1R and D2R-mediated signaling. To evaluate this model, we used homozygous D3R mutant mice and wildtype controls to investigate the role of the D3R in locomotor activity and stereotypy stimulated by acute amphetamine (AMPH) (0.2, 2.5, 5.0, 10.0 mg/kg). At the lowest dose tested (0.2 mg/kg), neither D3R mutant mice nor wild-type mice exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 38 publications
5
34
0
Order By: Relevance
“…In control mice, the response to amphetamine was apparently unaffected by the D3 dopamine receptor deletion (Fig. 1b), although there was an overall trend for an increase in locomotor activity in D3 dopamine receptor null mice (+/+;D3 -/- ) when the data were collapsed over treatment (p <0.05), consistent with a previous report (McNamara et al, 2006). …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In control mice, the response to amphetamine was apparently unaffected by the D3 dopamine receptor deletion (Fig. 1b), although there was an overall trend for an increase in locomotor activity in D3 dopamine receptor null mice (+/+;D3 -/- ) when the data were collapsed over treatment (p <0.05), consistent with a previous report (McNamara et al, 2006). …”
Section: Resultssupporting
confidence: 91%
“…There was an overall increase in locomotor activity of D3 dopamine receptor null mutants consistent with previous reports (Accili et al, 1996; McNamara et al, 2006; Xu et al, 1997). However, the D3 dopamine receptor antagonist S33084 had little effect on baseline and amphetamine-stimulated locomotor activity in normal mice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is assumed that psychomimetics stimulate motor and stereotypical activities of experimental animals through postsynaptic D 1 and D 2 dopamine receptors, while D 3 receptor stimulation inhibits locomotion [12,13]. On the other hand, it was shown that the yawning phenomenon is primarily caused by stimulation of presynaptic D 3 receptors, while D 2 autorecep- tors mediate its inhibition [11].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the computer allowed us to define a square center region (20 cm× 20 cm, edges 10 cm from each wall) and the total time spent in this region was quantified during each test stage. Besides the automated measures of motor activity, we quantified behavioral intensity in response to MP treatment using a rating scale adapted from McNamara et al (2006). Mouse behavior was scored from video recordings by a trained observer, blind to genotype and treatment condition, in 10 30-second intervals, starting at three and a half minutes and occurring every 4 minutes for 40 minutes (the length of the assay).…”
Section: Open Field Locomotor Activity and Locomotor Response To Acutmentioning
confidence: 99%